PENGARUH DISIPLIN BELAJAR, MOTIVASI BELAJAR DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI SMA MUHAMMADIYAH KOTA PAGAR ALAM - Firman Feriza (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
The purpose of this study is to determine: 1) Learning Discipline has a direct positive effect to learning achievement.2) Learning  Motivation has a direct positive effect to learning  achievement. 3) Family environment has a direct positive effect to achievement. 4) Learning  Discipline, Learning  Motivation,  and  Family Environment together  have  a direct positive  effect to learning achievement. This research  used  quantitative approach which data  and  information in formof numerical,  whereas research  type is Compositional Causal and Ex Post Facto. The population was 239 students,  while the sample  was 36 students (15%)  of the population. Technique for collecting the data  used  questionnaires and  documentation. The result of this study:1) The discipline of learning has a direct positive effect to the learning achievement of 0.112  (11.20%). 2) Motivation to learn does not give effect to learning achievement equal  to -0.333. 3) The family environment does not affect the learning achieve- ment  of -0.059  4) Learning  discipline,  motivation in learning,  and  family environment gave direct positive  effect to learning achievement of 0151  (15.10%).